MEDIA AND TOPICS RELATED TO EUROPEAN INTEGRATION OF SERBIA FOR THE PERIOD 2002-2016 - Marković Tomić, Milica Z (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
European integration of Serbia is defined as a long-term strategic goal of all Serbian governments, from 2002 to mid-2016, when the paper was written. To achieve this goal, Serbian politicians and experts emphasize the importance of public support and understanding of the EU integration among the Serbian citizens. Theory and practice, however, confirm the fact that it is very difficult to pass the unified message with unchanged meaning about the topic of such a strong public interest such is the topic European integration. Many communicators use various channels to convey the message of the European road, which again, provokes positive and negative attitudes, and even indifference among Serbian public. The views of Serbian citizens regarding joining the EU, monitored and measured through regular semi-annual public opinion polls, have evolved, from percentage of 72% of respondents who support to joining the EU at the end of 2002 to 41% in July 2016. The goal of this paper is to try to answer some of the questions related to formation and change of the attitudes of citizens of Serbia towards European integration, questions related communication process and communication actors, in an impartial manner and taking into account theory and official data, analysis of all actors involved in the process of informing the public on European issues, their messages and actions. This paper provides an analysis of the state of the European idea in Serbia. It uses the broader, more complete definition of the media, which encompasses all stages and actors in communication. Particular attention is paid to the analysis of the current state of the EU themes in Serbia, covering various aspects of the communication process, communication potentials in Serbia with segmentation of special communication actors and publics, as well as the obstacles and challenges in the context of communication of this topic.
Keywords: Serbia; media; public opinion; communications; European Integration